Upaya Meningkatankan Motivasi Belajar Melalui Layanan Konseling Kelompok bagi Siswa Kelas VII G SMP Negeri 2 Purwodadi Kabupaten Grobogan: Array - Titiek Suciati (Citra Dharma Cindekia, 2022)
The purpose of this research in general is to make improvements. The specific purpose of this research is the purpose of this Counseling Guidance Action Research is to increase learning motivation through group counseling services for class VII G students of SMP Negeri 2 Purwodadi semester 2 of the 2018/2019 academic year. This research is included in the type of action research with the design of Guidance and Counseling Action Research (PTBK), the purpose of this research is to make improvements. This Guidance and Counseling Action Research (PTBK) was carried out on class VII G students of SMP Negeri 2 Purwodadi in the even semester of the 2018-2019 academic year with two cycles, the number of students in this class was 32 children consisting of 16 boys and 16 girls, school location on Jalan P. Diponegoro No. 26 Purwodadi Grobogan, Central Java. The data analysis technique uses 1) descriptive qualitative, 2) descriptive comparative followed by reflection, the research procedure uses four stages in each cycle, namely planning or action planning, acting or carrying out actions, observing or observing, reflecting or reflecting. The results showed that there was a significant change, both seen from the results of the action and the service process, namely an increase in learning motivation which in the initial condition of students whose learning motivation was in the category of less than 11 students or (34.38%) and in the final condition in the second cycle there was less. 2 students or ( 6.25% ).